PENGARUH PROMOSI, HARGA, CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN LIQUID VAPOR PADA PERUSAHAAN 0274 E JUICE YOGYAKARTA - N, Antonius Jodhi; Wariati, Ambar; Dewi, Septiana Novita (KELOLA, 2018)
The purpose of this study is to examine the influence of promotion, price, and brand image to purchase decision of Liquid vapor at company 0274 E Juice Yogyakarta. The obtained by using sampling is accidental sampling. Then analyzed the data obtained in the form of qualitative and quantitative analysis, classical assumption test, multiple linear regression, t test, F, and R2. Based on the results of the analysis indicates that the validity and reliability test of all question items submitted proved valid and reliable. The results of the classical assumption test indicate that this study is normally distributed, does not occur multicollinearity, heteroscedasticity, and autocorrelation in the regression model. The result of multiple linear regression coefficient equation shows that promotion variable, price, and brand image have a positive effect on buying decision of Liquid vapor at company 0274 E Juice Yogyakarta. The result of t test shows that promotion, price, and brand image have positive and significant influence to Liquid vapor purchase decision. F test results indicate that there is a significant influence between promotion, price, and brand image simultaneously to the purchase decision of Liquid vapor. Meanwhile, the result of R2 test (coefficient of determination) obtained Adjusted R Square value of 0.652 means that promotion, price, and brand image variables contributed 65.2% to Liquid vapor purchase decision, while the rest of 34.8% influenced by other factors in outside the variables studied for example product quality, service quality, and consumer motivation.Keywords: promotion, price, Brand Image, Purchase Decision.